Motivational interviewing in medical care settings: A systematic review and meta-analysis of randomized controlled trials - Lundahl, B; Moleni, T; Butters, R; Burke, B; Tollefson, D; Butler, C; Rollnick, S (2013)
Objective: Motivational Interviewing (MI) is a method for encouraging people to make behavioral changes to improve health outcomes. We used systematic review and meta-analysis to investigate MI's efficacy in medical care settings. Methods: Database searches located randomized clinical trials that compared MI to comparison conditions and isolated the unique effect of MI within medical care settings. Results: Forty-eight studies (9618 participants) were included. The overall effect showed a statistically significant, modest advantage for MI: Odd ratio = 1.55 (CI: 1.40-1.71), z= 8.67, p< .001. MI showed particular promise in areas such as HIV viral load, dental outcomes, death rate, body weight, alcohol and tobacco use, sedentary behavior, self-monitoring, confidence in change, and approach to treatment. MI was not particularly effective with eating disorder or self-care behaviors or some medical outcomes such as heart rate. Conclusion: MI was robust across moderators such as delivery location and patient characteristics, and appears efficacious when delivered in brief consultations. Practice implications: The emerging evidence for MI in medical care settings suggests it provides a moderate advantage over comparison interventions and could be used for a wide range of behavioral issues in health care. © 2013.